SOIL EROSION UNDER DIFFERENT RAINFALL INTENSITIES, SURFACE ROUGHNESS, AND SOIL WATER REGIMES - Romkens M.J.M.; Helming K.; Prasad S.N. (My University, 2002)
Soil erosion is a complex phenomenon involving the detachment and transport of soil particles, storage and runoff of rainwater, and infiltration. The relative magnitude and importance of these processes depends on a host of factors, including climate, soil, topography, cropping and land management practices, control practices, the antecedent conditions, and the size of the area under consideration. In this study, the results of a series of experiments are reported, summarizing the soil loss and runoff response from a 0.6x3.75 m area to different rainstorm regimes, slope steepnesses, subsurface soil water pressures, and surface roughnesses under controlled laboratory conditions using a flume and rainfall simulator as water applicators, and a laser microreliefmeter and tensiometric system as soil response measuring devices. The soil chosen was a highly erodible Grenada loess (fine silty, mixed, thermic, Glossic Fragiudalf). The results showed: (1) a sequence of rainstorms of decreasing intensity on an initially air-dry smooth surface caused more soil loss than a sequence of similar storms of increasing intensity; (2) the surface roughness-sediment concentration relationship was not monotonic in nature; (3) subsurface soil water pressure substantially affected sediment concentration in runoff but only marginally impacted runoff amounts; (4) initially smooth, uniform surfaces may yield less soil loss than initially rough surfaces; (5) interrill runoff occurred as spatially varying flow in which flow patterns determine the locations of rills.
Keywords: EROSION PROCESSES; SEDIMENT CONCENTRATION; DRAINAGE NETWORKS; SURFACE MICRORELIEF; ROUGHNESS; SEEPAGE; SOIL WATER PRESSURE